Praetorianisme Orde Baru & Dampaknya Pada Relasi Sipil-Militer Era Reformasi (1999-2004) - Herdi Sahrasad (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2016)
The collapse of Soeharto’s military regime in May 1998 and the subsequent rise of a civilian regime under Baharuddin Jusuf Habibie have been embraced as the beginning of a new era of reform (era reformasi) in Indonesia. It was hoped at the time that Habibie would reform the country’s political system and initiate military reform, subjects which Soeharto had ignored for many decades. For this reason, radical students demanded that the new civilian regime consistently implement the demanded reforms, which included investigation and prosecution of Soeharto for his corruption, collusion, and nepotism, as well as the investigation and prosecution of the military on charges of human rights violations. They also called for peaceful solutions to be sought for separatist conflicts throughout the country.